The epidemiology of road traffic injuries in the republic of Serbia: a study based on hospital data, 2015-2019 - Rajčević, Smiljana; Štrbac, Mirjana; Kukić, Dragoslav; Marković, Marija; Ivanović, Ivan; Petrović, Radmila; Radić, Ivana (Frontiers in Public Health, 2024)
IntroductionRoad traffic injuries (RTI) are the leading cause of death and severe disability among individuals under the age of 40, posing a significant public health challenge globally. This manuscript highlights key aspects of the epidemiology of injuries in road traffic crashes (RTC) in Serbia, based on hospitalization report data.ObjectivesThe main aim of this study was to analyze the epidemiological characteristics of road traffic injuries (RTI) based on hospital data over a five-year period in Serbia.MethodsThe data for this study were obtained from the Hospitalization Report, which is part of the hospitalization database maintained by the Institute for Public Health of Serbia “Dr Milan Jovanović Batut,” covering the period from January 2015 to December 2019. The research included data from the Hospitalization Reports of 66 healthcare institutions across Serbia.ResultsDuring the study period, a total of 15,028 patients with road traffic injuries were admitted to healthcare institutions in Serbia. During the five-year period, the crude RTI incidence rate increased every year, from 39.0/100, 000 in 2015 to 43.7/100,000 in 2019. Older adult people aged 65 and over were particularly vulnerable as bicyclists and pedestrians (31.3, 27.7%, respectively). The Vojvodina region experienced a higher incidence of injuries among bicyclists compared and car accidents were most frequent in Central Serbia than in the other regions of Serbia. Craniocerebral injuries were the most common type of road traffic injury, accounting for 37.8% of cases. Significant differences in the types of injuries were observed based on age (χ2 = 649.859; p < 0.001) and gender (χ2 = 31.442; p < 0.001).ConclusionUnderstanding the epidemiological profile of road users involved in accidents is essential for monitoring and controlling specific risk factors. Our results highlight the need for enhanced traffic safety measures at the local level.